2014
DOI: 10.1002/hed.23805
|View full text |Cite
|
Sign up to set email alerts
|

Primary granulocytic sarcoma of larynx

Abstract: The detection of granulocytic sarcoma is difficult given its rarity and nonspecific presentation. To our knowledge, this is the second reported case of primary granulocytic sarcoma of the larynx reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Therefore, high clinical suspicion will improve the accuracy of diagnosis using CNB. Excision or debulking surgery may be considered for symptomatic patients with MS for improving the accuracy of their diagnosis and relieving their symptoms [6, 9, 16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, high clinical suspicion will improve the accuracy of diagnosis using CNB. Excision or debulking surgery may be considered for symptomatic patients with MS for improving the accuracy of their diagnosis and relieving their symptoms [6, 9, 16].…”
Section: Discussionmentioning
confidence: 99%
“…The 2008 World Health Organization (WHO) classification clarified the diagnosis of MS as follows: “a tumor mass consisting of myeloid blasts with or without maturation occurring at an anatomic site other than the bone marrow (BM)” [1, 3, 4]. MS has been described in 2.5–9.11% of patients with acute myeloid leukemia (AML) during the disease course [5, 6]. According to the 2016 WHO classification, MS may include the clinical presentation of any subtype of AML, present de novo (de novo MS), be accompanied by peripheral blood (PB) and BM involvement (MS with PB/BM involvement), present as relapse of AML (relapse of AML), or present as the progression of a prior myelodysplastic syndrome (MDS), myeloproliferative neoplasm (MPN), or both (progression of MDS/MPN) [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] It has been very rare where MS have been reported in association with acute promyelocytic leukemia, CML in blast crisis and myelodysplastic syndrome. [ 4 5 9 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] MS has been described in myriads of location, commonly in skin, gums, lymph nodes, and less often in bones, paranasal sinuses, larynx, orbit, breast, pleura, meninges, and central nervous system. [ 2 3 4 ] Although theoretically possible, MS involving the thyroid gland has never been reported in the English literature. MS is traditionally associated with acute myeloid leukemia (AML) orchronic myeloid leukemia (CML) in blast crisis.…”
Section: Introductionmentioning
confidence: 99%
“…Tsimberidou et al showed reduction in rate of progression to AML in isolated MS patients receiving systemic chemotherapy by 42% compared to patients receiving tumour localized treatment [12] . Isolated MS patients treated with AML based induction regimens have been reported to share similar prognostic features and prolonged disease-free interval [13] .…”
Section: Discussionmentioning
confidence: 99%